2021
DOI: 10.3390/toxins13040270
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Analysis Reveals a Compartmentalized Duct in the Venom Apparatus of the Wasp Spider (Argiope bruennichi)

Abstract: Spiders are one of the most successful groups of venomous animals, but surprisingly few species have been examined in sufficient detail to determine the structure of their venom systems. To learn more about the venom system of the family Araneidae (orb-weavers), we selected the wasp spider (Argiope bruennichi) and examined the general structure and morphology of the venom apparatus by light microscopy. This revealed morphological features broadly similar to those reported in the small number of other spiders s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…To evaluate the difference of smaller molecular proteins, further analysis by Tricine-PAGE was performed and showed HN-EVs to be largely in the molecular weight range of 9.5–35 kDa ( Figure 3 B). It has been shown that venom components can be transported into the gland lumen via EVs [ 27 ]. The protein profile of EVs in our study appears to be similar to that of the whole venom, though with different molecular weight distributions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the difference of smaller molecular proteins, further analysis by Tricine-PAGE was performed and showed HN-EVs to be largely in the molecular weight range of 9.5–35 kDa ( Figure 3 B). It has been shown that venom components can be transported into the gland lumen via EVs [ 27 ]. The protein profile of EVs in our study appears to be similar to that of the whole venom, though with different molecular weight distributions.…”
Section: Resultsmentioning
confidence: 99%
“…Exosomes are released into the extracellular environment upon fusion of multi-vesicular bodies (MVBs) with the plasma membrane [ 28 ]. The apical portion of the glandular epithelium cells is rich in secretory vesicles, according to structural and ultrastructural descriptions of the venom glands of Loxosceles intermedia [ 23 ], Cupiennius salei [ 24 ], Agelena labyrinthica [ 25 ], Vitalius dubius [ 26 ], and Argiope bruennichi [ 27 ]. In this study, transmission electron microscopy revealed the MVB structure in the glandular epithelium cells of the Ornithoctonus hainana venom gland, as well as an exosome-like vesicle structure in the lumen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncontrolled microbial infection in such an environment could lead to rapid replication and potentially lethal infections. The gland is connected to the chelicerae by a venom duct [ 42 , 43 ]. The envenomation of targets (attackers or prey) therefore provides an opportunity for inoculation with microbes that could develop into an infection.…”
Section: Discussionmentioning
confidence: 99%
“…In case of the established snake venom gland organoids, the utilization of a mammalian growth factor cocktail seemingly allows a virtual indefinite culturing ( Post et al, 2020 ). The compartmentalized nature of venom systems, in which distinct areas produce different components of the venom, are also maintained in venom gland organoids ( Tayo et al, 2010 ; Hu et al, 2011 ; Undheim et al, 2014 ; Valente et al, 2018 ; Post et al, 2020 ; Schmidtberg et al, 2021 ). Furthermore, given that organoids faithfully produce venom components, they can be used to culture venom glands from animals that are difficult to study even by venomics, to obtain larger amounts of venom for functional analysis.…”
Section: How Synthetic Biology Enables Access To Venom Gene Productsmentioning
confidence: 99%